Body Image Objectification and Disordered Eating Attitudes Among Secondary School Students of South-West Nigeria - Olaide N Koleoso; Oluyemi O Akanni; Joy O James (Shiraz University of Medical Sciences, 2018)
Background: Research on body image objectification in Nigeria is scanty, particularly with regards to disordered eating attitudes. Thus, this study examined the relationship between the 2 constructs among secondary school students in the country. Methods: Overall, 270 students were selected through convenience sampling from 3 schools randomly selected from a local government area in South West Nigeria, and completed a questionnaire containing the 26-item eating attitudes test (EAT-26) and objectified body consciousness scale (OBCS). The students were classified to 2 groups using the EAT-26 cut-off point of 20, and the differences in the mean scores of the 3 sub-scales of OBCS were determined between the groups. Results: There were more females than males (56.7% vs. 43.3%) with a mean age of 16.1 years. Eighty-five students scored above the cut-off point of 20, thus, prevalence rate of disordered eating attitudes was 31.5%. There was no significant association between the socio-demographic variables and disordered eating attitudes. The appearance control belief (a subscale of OBCS) was significantly lower in students with disordered eating attitudes (t = 2.18, P = 0.03), whereas, the remaining 2 subscales of OBCS was not significantly associated with disordered eating attitudes. Conclusions: Appearance control belief seems to be the most important in the eating attitudes of Nigerian adolescents in self-objectification. However, more research is needed to shed more light on this matter.